Essays in Empirical Macroeconomics - Byrne, Stephen Christopher (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2025)
This thesis is a collection of three independent essays. The objective of the research is to answer three major questions faced by Central Banks and policymakers in Europe that have arisen since the Global Financial Crisis. The first essay examines the "wage puzzle" in Europe during the period from 2012 to 2017, where wage growth remained markedly subdued despite significant reductions in conventional measures of labour market slack. The contribution of this chapter is to generate a "non-employment index" (NEI) for a selection of European countries using a novel dataset that exploits the panel structure of the European Labour Force Survey. The NEI includes discouraged workers and those marginally attached to the labour market, but crucially, their weight in the index is determined by their estimated probability of transitioning back into employment. We demonstrate that using the NEI in a wage Phillips curve more accurately accounts for the wage dynamics across several Eurozone countries. The implication is that conventional measures of labour market slack understate the available pool of labour when cyclical conditions tighten. We show that this effect is stronger in those countries most affected by the sovereign debt crisis. The second essay makes two significant contributions to the literature on capital misallocation and the broader debate on productivity divergence across Europe. First, it provides a comprehensive measurement and decomposition of the sources of capital misallocation across 19 European countries. Using a novel dataset containing firm-level balance sheet data from the manufacturing sector, we employ the methodological framework of David and Venkateswaran (2019), which accounts for adjustment costs and firm-level uncertainty. In contrast to previous studies, which primarily focus on country-level estimates, we extend the analysis to industry-level variation. By decomposing misallocation at the two-digit NACE industry level, we document substantial heterogeneity in the factors driving misallocation across sectors and countries. Our findings show that most of the observed dispersion is driven by permanent firm-specific factors, particularly in Southern European countries that were more severely impacted by the sovereign debt crisis. We also identify significant contributions from adjustment costs and uncertainty, whereas firm-specific distortions play a more limited role. Second, the chapter shows that financial variables and productivity-related industry characteristics are closely linked to the persistent distortions observed in our analysis. This provides new insights into the role of financial and macroeconomic conditions in driving productivity differences across Europe, highlighting the importance of targeted policy interventions to address these sources of misallocation. The third chapter addresses whether macroprudential policies designed to stabilise traditional banks inadvertently shifted credit activity into less-regulated non-bank financial intermediaries (NBFIs), and if so, how this shift affects the transmission of monetary policy. Using a panel of European countries from 2009 to 2021 and comprehensive data on macroprudential policies from the IMF, I show that a tightening of macroprudential policies on traditional banks is associated with an increase in financial vehicle corporation (FVC) loans. This finding supports the "cross-sectoral arbitrage" hypothesis proposed by Farhi and Tirole. Second, the analysis finds that loan-targeted macroprudential measures do not appear to significantly influence this shift, suggesting that policies aimed at systemic risk, such as capital requirements and the use of bank profits, are the main drivers of the result. Finally, the chapter investigates how FVC loans respond to monetary policy shocks. Contrary to the traditional bank lending channel, FVCs are found to expand their lending following a monetary policy shock. This finding provides suggestive evidence that the expansion of FVCs, spurred by macroprudential tightening, may also dampen the transmission of monetary policy to the broader financial system.
APPROVED
Keywords: Economic Growth; International Macroeconomics